Three new species of Rhyacophila (Trichoptera: Rhyacophilidae) from Taiwan and Nepal - Kiss, Ottó (Zootaxa, 2013)
Three new species of the Rhyacophila scissa Group in the genus Rhyacophila (Trichoptera, Rhyacophilidae), i.e., Rhya-cophila matanyii n. sp. from Taiwan (Republic of China), Rhyacophila steinmanni n. sp. and Rhyacophila kisszoltani n. sp. from Nepal are described and illustrated with drawings of the genitalia.